Health Education pada Masyarakat Penderita TB Paru terhadap Pencegahan Risiko Menular - Rahma Tunny; Mirdat Hitiyaut; Ernawati Hatuwe (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
TB is a serious infection caused by the Mycobacterium tuberculosis. Even now, tuberculosis paru remains one of the world's most pressing health issues. Even though many nations have taken steps to combat this illness, if it is not treated, it could lead to kematian. The goal of health promotion is to increase awareness of how to prevent tuberculosis in children. In order to conduct a thorough investigation, this community's pengabdian uses a quantitative approach and a kuesioner's lembar to understand the experiences of TB patients and other members of the community. Following the dissemination of health education about TB Paru to the general public at Puskesmas Negeri Lima, the general public's knowledge increased by 70–80%. This score is higher than the pre-test score of roughly 62%. This health education is provided in a gentle manner via ceramah, discussion, and tanya jawab. The results of the test indicate that the general public's knowledge has increased.